FREQUENCY, STRUCTURE, AND DYNAMICS OF ADENTIA DEVELOPMENT AND RELATED SECONDARY DENTAL DEFORMATIONS AMONG YOUNG PEOPLE - Beliaiev, E.V.; Filimonov, V.Yu.; Dmitriev М.О.; Zakalata, T.R. (World of Medicine and Biology, 2020)
As part of the epidemiological survey study on dental health in young people, the data of clinical dental examination of 137 boys and 142 girls, the students of dental faculty of Vinnytsya National Pirogov Memorial Medical University, were analyzed. For comparative analysis of the structure of adentia the data of epidemiological study held in 2010 on the the Department of Orthopedic Dentistry were used. Statistical processing of the results was carried out in the Statistica 6.0 licensed package. The comparison of structure and frequency of adentia of young population in 2010 and 2019 revealed a decrease of frequency of this pathology. Change of the structure of adentia toward the relief of orthopedic pathology due to the significant decrease of adentia in the form of edentulous areas located posterior to the remaining natural teeth according to the topography should also be emphasized. A significant frequency of secondary deformations in the examined group with the prevalence of horizontal form was identified. In the structure of adentia there is a ninefold prevalence of adentia in the posterior area above the anterior one, a significant prevalence of adentia of the lower jaw.